(untitled) (Conferencea, 2023)
There are several methods of teaching using pedagogical technologies in the production of sulfuric acid in industry. The benefits of using advanced teaching methods such as e-learning platforms, virtual reality simulations and interactive multimedia content to improve the learning experience and results for students and professionals were discussed.